Development of RME Based Mathematics Learning Tools to Improve Students' Problem-Solving Abilities and Independence - Harahap, Shahnaz Shafitri; Hasratuddin, Hasratuddin; M.Simanjorang, Mangaratua (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to describe: Validity, practicality and effectiveness of LKPD based on realistic mathematics learning approach developed towards improving students' problem solving ability and independence through LKPD based on realistic mathematics learning approach developed.: This study is a development research using Tessmer development model formative evaluation type. This development model consists of 2 stages of development, namely introduction (determination) and prototyping (design and evaluation). From the results of trial I and trial II obtained: LKPD based on realistic mathematics learning approach to improve students' problem solving ability and Learning Independence developed has met the criteria of valid, practical and effective; Improvement of problem solving ability using LKPD based on realistic mathematics learning approach that has been developed seen from the N-gain value in trial I of 0.35 increased to 0.39 in trial II, meaning it is in the